IMPLEMENTING LITERATURE CIRCLES TO PROMOTE STUDENTS’ ENGAGEMENT IN READING COMPREHENSION ACTIVITIES - Komara, Khairunnisa; Puspitaloka, Nina; Rahmawati, Maya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study explored the implementation of Literature Circles in promoting students’ engagement during reading comprehension activities in an English as a Foreign Language (EFL) classroom. The study employed a qualitative case study design involving one English teacher and eighth-grade students at a junior high school in Karawang, Indonesia. Data were collected through classroom observation and semi-structured interviews with the teacher and six students. The findings revealed that Literature Circles were implemented through several stages, namely preparation, individual reading, group discussion, sharing and reflection, and teacher feedback. The implementation encouraged students to participate actively during reading activities through collaborative discussion and role-based interaction. Students also demonstrated positive engagement by sharing ideas, helping peers, discussing vocabulary, and participating during group discussions. Furthermore, the activity increased students’ motivation and involvement in reading English texts. However, several challenges were identified, such as unequal participation, vocabulary difficulties, and nervousness during presentations. Overall, Literature Circles can support collaborative and interactive learning environments that promote students’ engagement during reading comprehension activities.